Faktor-faktor yang Mempengaruhi Kepuasan Kerja Perawat PK 3 - Fahrudin, Arif; Mulyati, Mulyati; Rohayani, Lilis; Asmirajanti, Mira; Oyoh, Oyoh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the factors that influence job satisfaction of nurses in the PK 3 category at Cibinong Regional General Hospital, Bogor Regency. The study design used Explanatory Research with a Cross Sectional approach. The population in this study were 157 nurses at the Cibinong Regional General Hospital level PK 3. The number of samples in this study was 157 respondents. Data collection used research instruments that had been tested for validity and reliability. Data analysis used statistical applications including univariate, bivariate, and multivariate analysis. The results of the study, all variables were proven to have a significant effect on job satisfaction (p < 0.05). High motivation increased the chance of job satisfaction by 569 times, followed by interpersonal relationships (111 times), supervision (76 times), and light workload (62 times). A comfortable work environment, career development, and management support also made a positive contribution. Conversely, the perception of dissatisfaction with satisfaction significantly decreased job satisfaction. In conclusion, management support and related factors have a strong influence on nurse job satisfaction. Improving motivation, managing workload, interpersonal relationships, supervision, and a fair compensation system are essential to improving job satisfaction. Keywords: Workload; Interpersonal Relationships; Job Satisfaction; Motivation